EVALUASI LAYANAN SIRKULASI PERPUSTAKAAN POLITEKNIK NEGERI BALI - Evarini, Ni Ketut; Suhartika, I Putu; Haryanti, Ni Putu Premierita (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2016)
ABSTRACT The title of this study is Evaluation of Library Circulation Services Bali State Polytechnic..This research is located at Bali State Polytechnic Library. The population of this research is the students who are members of the Polytechnic Library Bali in March 2016 as many as 112 people. The research sample is calculated using the formula slovin, with a total sample of 87 people, while the sample collection technique used was stratified random sampling. The results obtained in this study can be explained that the circulation of Bali State Polytechnic Library met the needs of library users so as to achieve the satisfaction of library users, judging from hypothesis testing showed that the t value is smaller than alpha (? = 0.005) to 0.000 < 0.005, it can be said that the circulation service can influence user satisfaction at Bali State Polytechnic Library. Keywords: Circulation Service, User Satisfaction, Library.